SIKAP ANGGOTA DPRD KABUPATEN BANYUMAS TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH - Noer Indriati; Muhammad Taufiq; Wismaningsih Wismaningsih (Jurnal Idea Hukum, 2019)
The community has the authority to regulate and resolve the matter themselves according to local aspirations. It is clear that the position of trying to reassert the community is the subject of autonomy is not the object of autonomy. The decentralization policy explicitly also uncover the essence of autonomy as authorities set up and take care of his household. The aim’s to analyze the against public participation in rulemaking. The method of the research is socio legal approach, the data sources used are primary data and secondary data, with analysis in quantitative diskriptif.Results of the research as follows: the participation of youth in the formation of Regulatory Region of Pilkades 50% of respondents indicate a very high participation,. Participation of mothers PKK/dawis high participation 43.54 and the general public towards 35.51% showed very high participation, 60.98% of respondents participated in height and 2.91% of respondents indicating participation is quite high. The participation of notable clerics against Perda Pilkades 42.4% of respondents indicate a very high participation, 46.40% of respondents indicate high participation and 7% of respondents indicating participation is quite high.